Esophageal conduit in nearly hopeless corrosive esophageal stricture patient - Laohapensang K. (2014)
The case report of a 28 year old woman with strictured esophagus from corrosive esophagitis for 4 months is presented. Barium swallowing showed a strictured esophagus extending from T2 to the aortic knob and needed frequent dilatations. The patient had a perforated thoracic esophagus and mediastinitis on last dilatation. Cervical esophagostomy, transabdominal esophageal bandaging and jejunostomy feeding were done along with intravenous broad spectrum antibiotics. On esophagoscopy, there was complete stenosis of the cervical esophagus 2 cm from the postcricoid area. The large intestine from the caecum, transverse colon and descending colon was chosen as the esophageal conduit because of adequate length to pass subcutaneously. The caecum was anastomosed to the cervical esophagus and descending colon to the stomach. Seven days postoperatively, the patient could take liquids and soft porridge orally. There was a small leakage from the cervical anastomosed, spontaneous closure was achieved 3 weeks postoperatively. We chose the right side colon as the esophageal conduit because of adequate length to pass subcutaneously. Mediastinal and transhiatal routes could not be passed because of previous mediastinitis from thoracic esophageal perforation. This may be an alternative choice of operation for high cervical esophageal stenosis with previous mediastinitis.